Phonetic complexity affects children’s Mandarin tone production accuracy in disyllabic words: A perceptual study - Wong, Puisan; Strange, Winifred (PloS one, 2017)
This is the first study to examine the effect of phonetic contexts on children's lexical tone production. Mandarin tones in disyllabic words produced by forty-four 2- to 6-year-old children and twelve mothers were low-pass filtered to eliminate lexical information. Native Mandarin-speaking adults categorized the tones based on the pitch information in the filtered stimuli. All mothers' tones were categorized with ceiling accuracy. Counter to the findings in most previous studies on children's tone acquisition and the prevailing assumption in models of speech development that children acquire suprasegmental features much earlier than segmental features, this study found that children as old as six years of age have not mastered the production of Mandarin tones. Children's tones were judged with significantly lower accuracy than mothers' productions. Tone accuracy improved, while cross subject variability in tone accuracy decreased, with age. Children's tone accuracy was affected by the articulatory complexity of phonetic contexts. Children made more errors in tone combinations with more complex fundamental frequency (F0) contours than tone sequences with simpler F0 changes. When producing disyllabic tone sequences with complex F0 contours, children tended to shift the F0 contour of the first tone to reduce the F0 change, resulting in more tone errors in the first syllable than in the second syllable and showing substantially more anticipatory coarticulation than adults. The results provide further evidence that acquisition of lexical tones is a protracted process in children. Tones produced accurately by children in one phonetic context may not be produced correctly in another phonetic context. Children demonstrate more anticipatory coarticulation in their disyllabic productions than adults, which may be attributed to children's immature speech motor control in tone production, and is presumably a by-product of their inability to accomplish complex F0 changes within the syllable time-frame.